A combination treatment of transanal total mesorectal excision and Turnbull–Cutait abdominoperineal pull-through procedure for a low rectal cancer - Celik,Suleyman Utku (2019)
ABSTRACT Surgical treatment for low rectal cancer has changed dramatically during the preceding several decades, and the optimal surgical approach remains incompletely developed. Transanal total mesorectal excision is likely the most promising approach for the dissection of the distal part of the mesorectum in a manner that allows for a technically easy and oncologically safe operation. Long after it was first described, the Turnbull–Cutait abdominoperineal pull-through procedure has recently been reintroduced in surgical practice for the treatment of patients with complex anorectal conditions. The current report describes a case of distal rectal cancer involving successful surgical treatment with a combination of the two aforementioned methods and patient discharge without a diverting stoma.